PENGUJIAN KEMBALI PUTUSAN PRAPERADILAN TENTANG SAH ATAU TIDAKNYA PENETAPAN TERSANGKA PUTUSAN NOMOR 1/Pid.Prap/2022/PN Sos - Kolono, Sucipto; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This research focuses on examination or testing and public judgment, because examination aims to encourage law enforcers, such as judges and prosecutors to uphold the law based on good judgment, the research used is normative, through secondary data such as laws and regulations, court decisions, expert opinions and legal norms. So the author is interested in examining Pretrial Decision Number 1/Pid./2022/PN Sos at the Soasio District Court of Tidore Islands, North Maluku, this case involves Ailen Goeslaw, as Head of the Youth and Sports Office (KADISPORA), to see if it is in accordance with the legal process in Pretrial regarding the Determination of Suspects, at that time suspected of committing Corruption Crime related to the Construction of the Maba City Stadium, East Halmahera, North Maluku. Ailen Goeslaw was named as a suspect by the East Halmahera District Attorney's Office because it was deemed sufficient to fulfill two pieces of evidence related to the State financial losses incurred. Through his attorney, Ailen Goeslaw then filed a pretrial to test whether the determination as a suspect was in accordance with legal procedures. However, the judge of the Soasio District Court, Tidore Islands, North Maluku. Decided that the determination of the suspect was in accordance with legal procedures,Keyword: .Public examination, Preterial, Suspect determination, .coruption